2014
DOI: 10.1039/c3nr05851d
|View full text |Cite
|
Sign up to set email alerts
|

High-purity iron pyrite (FeS2) nanowires as high-capacity nanostructured cathodes for lithium-ion batteries

Abstract: Iron pyrite is an earth-abundant and inexpensive material that has long been interesting for electrochemical energy storage and solar energy conversion. A large-scale conversion synthesis of phase-pure pyrite nanowires has been developed for the first time. Nano-pyrite cathodes exhibited high Li-storage capacity and excellent capacity retention in Li/pyrite batteries using a liquid electrolyte, which retained a discharge capacity of 350 mAh g(-1) and a discharge energy density of 534 Wh kg(-1) after 50 cycles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
131
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(139 citation statements)
references
References 50 publications
6
131
2
Order By: Relevance
“…The mineral is an abundant and inexpensive material being researched as a cathode material for Li-ion and Na-ion batteries. [94][95][96] In the 80's attempts to utilize it for Al batteries were made but without any commercial value. [97] As the material has a very high theoretical capacity i.e., 894 mA h g −1 applications related to energy storage can be very appealing.…”
Section: Fes 2 (Pyrite)mentioning
confidence: 99%
“…The mineral is an abundant and inexpensive material being researched as a cathode material for Li-ion and Na-ion batteries. [94][95][96] In the 80's attempts to utilize it for Al batteries were made but without any commercial value. [97] As the material has a very high theoretical capacity i.e., 894 mA h g −1 applications related to energy storage can be very appealing.…”
Section: Fes 2 (Pyrite)mentioning
confidence: 99%
“…Amorim et al 116 and Caban-Acevedo et al When the precursors are prepared by a specic method, the products usually have the same or similar morphology with their precursors. For instance, Li et al 122 used FeF 3 $3H 2 O nanowire, as precursor to prepare iron pyrite, prepared by solution synthesis, and the morphology of the products aer sulphidation was also nanowires (Fig. 7a and b).…”
Section: Sulphidation Synthesis Of Iron Pyrite With Different Morpholmentioning
confidence: 99%
“…FeS 2 has many appealing properties such as a bandgap in the range of 0.8-0.95 eV, 19 a large optical absorption coefficient (λ ≤ 700 nm, α ≥ 5×10 5 cm −1 ), 20 high-carrier mobility (for single crystals), 21 non-toxicity, and environmental compatibility. 22 Therefore, FeS 2 has attracted particular interest as a material for energy-conversion applications such as electrodes for dye-sensitized solar cells (DSSCs), 20 lithium-ion batteries (LIBs), 23,24 thermal batteries, 25 photocapacitors 26 and electrocatalyst for the oxygen reduction reaction (ORR). 27 Only a small number of studies have been reported on hydrogen production using FeS 2 electrocatalysts.…”
mentioning
confidence: 99%